Kebijaksanaan Pembangunan Perkotaan Di Indonesia: Aspek-Aspek Penting Untuk Operasionalnya - Budhy Tjahjati S Soegijoko (The Institute for Research and Community Services, Institut Teknologi Bandung, 1995)
In the future, there will be a shift in the pattern of managing urban development activities. Conventional method that is oriented more on the physical aspect relied more on the government ideas and initiative, referred more on the historical development trend and more